Molecular Genetics of Bacteria - Snyder, Larry Champness, Wendy (ASM Press, 1997)
This advanced-level textbook offers an in-depth look at molecular biology and biochemistry. The diversity of bacterial genetics is explored in discussions of microbial systems beyond the much-studied E coli. Much-used information is included inside the front cover for easy reference.